PENGGUNAAN HUMAN MACHINE INTERFACE UNTUK SIMULASI PENGOLAHAN MINYAK KELAPA SAWIT - Stefan Adriel; Melisa Mulyadi; Budi Kartadinata; Linda Wijayanti (Jurnal Elektro, 2020)
Technological developments have brought changes in the industry, the process that was originallydone by humans has turned to the automation system. In this paper the application of the automationsystem is carried out on the processing of palm oil. The system is made in the form of a simulation ofan automation system using the Programmable Logic Controller (PLC) and Human MachineInterface (HMI). Automation of palm oil processing using PLC with the help of Unity Pro XLsoftware, monitoring processes using HMI with the help of Vijeo Designer Basic software, and analoginput simulated using a potentiometer. PLC receives and processes data from both analog inputs andfrom HMI. The process of cooking and extracting palm oil carried out by the PLC is displayed on theHMI. From the test results, it is known that the PLC can communicate with HMI and HMI can displaythe processes that occur in palm oil processing.